Promotion of bowel elimination ostomy self-care: A qualitative study based on the nurses' and patients' perspectives - Igor Emanuel Soares-Pinto; Sílvia Maria Moreira Queirós; Paulo Jorge Pereira Alves; Célia Samarina Vilaça de Brito Santos; Maria Alice Correia Brito (Tehran University of Medical Sciences, 2022)
Background & Aim: The construction of an ostomy has a physical, psychological, and social impact, requiring the need to adapt. The way this event is experienced is influenced by several factors, namely ostomy self-care competence, the aspect most referred to in the literature. Nurses' specific and systematic intervention positively influences the person's adaptation to the ostomy. This study aimed to describe the perception of nurses and people with ostomies about promoting ostomy self-care. Methods & Materials: A qualitative descriptive study was conducted. Semi-structured interviews were conducted with ten nurses specializing in stoma therapy and twelve people with bowel elimination ostomy. Content analysis was performed according to Bardin with categorical analysis. Results: Two themes emerged from the interviews: the promotion of awareness, with three categories and four sub-categories, and the promotion of ostomy self-care, with five categories and twenty-four sub-categories. In promoting awareness, the participants mentioned key contents that could be included in the nurse's approach: assessing awareness, content for promoting awareness, and awareness indicators. Within the scope of promoting self-care, categories emerged, such as the intervention standardization, the contents, the methodologies, and the resources to promote self-care. Conclusion: This study adds to evidence about promoting awareness of bowel elimination ostomy and self-care competence after the procedure. These results can be useful for nurses, allowing them to reflect on clinical practice and helping to improve the planning of their intervention in promoting stoma self-care.